Gobierno autónomo o de libre albedrío: una contribución al diseño de estándares en el subproceso de reclutamiento y selección de personal para servicio ocasional en los GAD’s de Yantzaza y Centinela del Cóndor, año 2024 - Hurtado Alverca, Diana Alejandra (2024)
The purpose of this curriculum integration work was to develop a standard that regulates the sub-process of recruitment and selection of personnel for occasional service in the Human Resources departments of the Autonomous Decentralized Governments of Yantzaza and Centinela del Cóndor, for this purpose, In addition, it was verified that in these municipalities the subprocess is carried out directly, without making an open call so that several candidates can participate and thus be able to select the ideal profile for the vacant position. In view of the above, the design of the standard was proposed as an alternative solution in human talent management and thus generate and ensure a transparent and effective sub-process for the two entities, it should be noted that use was made of the document, Methodology for the survey of processes of the National University of Loja. The methodology applied for the elaboration of the research work was based on the use of the qualitative method, for which research instruments were used (semi-structured interviews and observation sheets), which made it possible to obtain relevant information for the elaboration of the proposed solution, With respect to the type of research, it was possible to use the information analysis tools PESTEL and AMOFHIT, which contributed to the situational diagnosis and in this way a TOWS matrix was elaborated based on the internal and external analysis of the department, with the objective of designing strategies that contribute to the needs of human talent management.